International nuclear non-prolieferation system: challenges and choices - Simpson, John (ed.); McGrew, Anthony G. (ed.) (London, 1984)
Nuclear proliferation has been a feature of the international political system for the last forty years, ever since the fears of a German nuclear weapon stimulated the US Manhattan Project into producing the first atomic bomb. Since then four additional states have acquired a nuclear stockpile. It was not until. the 1960s, however, that an East-West consensus was created on the measures needed to control nuclear proliferation. This i consensus was formalised in the Non-Proliferation Treaty, which was signed in 1968 and came into force in 1970. Since. then there have been conferences to review the operation of the Treaty in 1975 and 1980, and in September 1985 a further conference will be convened for this purpose. In 1995 the Treaty lapses unless its parties choose to extend its life. Although 1995 may appear rather distant, fears are growing that Third-World disenchantment with the workings of the Treaty will lead to its demise as a near-universal instrument for preventing nuclear proliferation.
Keywords: Atomic weapons and disarmament